ASSET AND LIABILITY MANAGEMENT (ALM) STRATEGY IN MICROFINANCE INSTITUTIONS FOR LONG-TERM FINANCIAL STABILITY - Gunawan Widjaja (BORJUIS: JURNAL OF ECONOMY, 2024)
Managing assets and liabilities is very important because disbursement of funds and distribution of funds in the form of credit must be carried out in order to optimize the funds collected to gain profits for the bank. ALM is a process of planning, organizing and monitoring which functions as integrated control of assets and liabilities which are interconnected in an effort to achieve profits for microfinance institutions. The method used is a literature review. Writing this discussion uses information procedures regarding the discussion, in the form of previous research, then reviewing and analyzing various sources related to the discussion raised by the researcher. This research discusses the theory of asset and liability management, a review of the basic concepts and importance of ALM, an introduction to the role and challenges of MFIs in the economy, long-term financial stability, and a discussion of the factors that influence MFI financial stability.